Research in consumer behavior. Vol. 14 - Belk, Russell W.; Askegaard, Søren; Scott, Linda M. (Research in consumer behavior., 2012)
This volume presents selected papers from the 7th Annual Consumer Culture Theory Conference held at Oxford University in August, 2012. The 18 papers in the volume together capture the latest research within this qualitative paradigm of consumer studies. Topics addressed cover a wide gamut including immigrant consumption experiences, gift-giving, sharing, transgressive gender roles, attachments to special possessions in online games and real life, the homeless consumer experience, disposition of possessions, privacy, metaphor analysis, sustainable consumption, alcohol consumption, cosmetics usage, and the negative consequences of sponsoring children in the less affluent world.